The Oncogenic Burden of Obesity: Mechanistic Links Between Adiposity and Gastrointestinal Cancers—A Comprehensive Narrative Review - Felicia Lee; Jessica Moore; Mariam Markouli; Wissam Ghusn (Biomedicines, 2025)
Obesity is a global health crisis with profound implications for cancer risk, particularly within the gastrointestinal (GI) tract. Mounting evidence demonstrates that excess adiposity contributes to the initiation, progression, and poor outcomes of GI malignancies through a constellation of interrelated mechanisms. This review comprehensively examines the biologic pathways linking obesity to cancers of the esophagus, stomach, colon, liver, pancreas, and gallbladder. Chronic low-grade inflammation, driven by adipose tissue-derived cytokines and immune cell infiltration, plays a central role in tumorigenesis via the activation of NF-κB, STAT3, and other pro-oncogenic signaling cascades. Hyperinsulinemia and insulin resistance increase mitogenic IGF-1 signaling, while dysregulated adipokines, particularly elevated leptin and reduced adiponectin, promote cellular proliferation and impair tumor suppression. Dysbiosis of the gut microbiome and alterations in bile acid metabolism generate carcinogenic metabolites that contribute to DNA damage and immune evasion. Additionally, obesity-induced tissue hypoxia fosters tumor growth through HIF-1α-mediated pathways. We further highlight organ-specific associations, such as visceral adiposity’s role in Barrett’s esophagus and hepatocellular carcinoma emerging from metabolic dysfunction-associated steatotic liver disease (MASLD). Importantly, emerging data suggest that weight loss, achieved via lifestyle, pharmacologic, or surgical interventions, may mitigate these carcinogenic pathways and improve tumor biology. As obesity prevalence continues to rise globally, elucidating its mechanistic ties to GI malignancies is essential for risk stratification, prevention strategies, and personalized care. By integrating epidemiologic and molecular insights, this review underscores the need for multidisciplinary approaches to curb the oncogenic burden of obesity and improve outcomes in GI oncology.